Analisis Pengaruh Non Performing Financing (NPF), Financing To Deposit Ratio (FDR), Inflasi dan Capital Adequacy Ratio (CAR) terhadap Proporsi Pembiayaan Murabahah pada Bank Umum Syariah di Indonesia - Haqqi, Hibatul; Dr.Triyono, SE.. M.Si (2016)
The purpose of the research is to analyze the influence Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Inflation and Capital Adequacy Ratio (CAR) to proportion of Murabahah on the Islamic banks in Indonesia 2012-2014. The population in this research is a quarterly financial report of entire Islamic Banks in Indonesia and the rate of inflation. The sampling technique is purposive sampling method with predefined criteria. from the sample of criteria predefined amount of data obtained in accordance with the criteria is as much as 72 quarterly financial report of 6 Islamic Banks. The analytical tool used in this research is SPSS version 21. The results showed that the NPF, FDR, Inflation and CAR simultaneously affect the murabaha financing. The amount of the effect of the five independent variables on the proportion of murabaha financing amounted to 36.2% and the remaining 63.8% is influenced by other variables outside of of this research. While for the results of the partial, variable NPF positive effect on the proportion of murabaha financing, CAR negative effect on the proportion of murabaha financing. While FDR variables and inflation do not have a significant effect on the proportion of murabaha financing.